2016
DOI: 10.4238/gmr.15038252
|View full text |Cite
|
Sign up to set email alerts
|

Serum microRNA-135a downregulation as a prognostic marker of non-small cell lung cancer

Abstract: ABSTRACT. Abnormal expression of microRNA-135a (miR-135a) is closely associated with oncogenesis. However, the relationship between serum miR-135a levels and the clinical parameters and prognosis of non-small cell lung cancer (NSCLC) remain unclear. The study aimed to investigate the clinical significance of serum miR-135a expression in patients with NSCLC. miR-135a expression was analyzed by realtime PCR and its correlation with NSCLC was determined by various statistical methods for 104 NSCLC patients and 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…AUC of both predicted the prognosis of patients exceeded 0.80, indicating that both had higher prognostic value and might be independent prognostic indicators for NSCLC patients. In the studies by Zhang et al [28], the level of serum miR-135a is significantly lower in NSCLC patients, which is consistent with our research results. It has also pointed out that high level of miR-135a is significantly related to patients' distant metastasis, high TNM staging, low level of 5-year OS and other adverse prognosis.…”
Section: Discussionsupporting
confidence: 93%
“…AUC of both predicted the prognosis of patients exceeded 0.80, indicating that both had higher prognostic value and might be independent prognostic indicators for NSCLC patients. In the studies by Zhang et al [28], the level of serum miR-135a is significantly lower in NSCLC patients, which is consistent with our research results. It has also pointed out that high level of miR-135a is significantly related to patients' distant metastasis, high TNM staging, low level of 5-year OS and other adverse prognosis.…”
Section: Discussionsupporting
confidence: 93%
“…14 More than 50% of the miRNA genes have been located in tumor-related genomic regions or fragile sites. 28 Zhou's findings indicated that miR-135a promotes cell apoptosis and inhibits cell proliferation, migration, invasion, and tumor angiogenesis by targeting IGF-1 gene through the IGF-1/PI3K/Akt signaling pathway in NSCLC, 29 and MiR-135a inhibits migration and invasion and regulates EMT-related marker genes by targeting KLF8 in lung cancer cells, 30 which is consistent with our study, while Zhang's study showed that MiR-135a overexpression promoted viability, migration, and invasion, but inhibited apoptosis of NCI-H1650 and NCI-H1975 cells. The serum miR-135a level was downregulated in non-small-cell lung carcinoma (NSCLC) patients and was associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…It can be used as a biomarker for NSCLC prognosis. 28 Zhou's findings indicated that miR-135a promotes cell apoptosis and inhibits cell proliferation, migration, invasion, and tumor angiogenesis by targeting IGF-1 gene through the IGF-1/PI3K/Akt signaling pathway in NSCLC, 29 and MiR-135a inhibits migration and invasion and regulates EMT-related marker genes by targeting KLF8 in lung cancer cells, 30 which is consistent with our study, while Zhang's study showed that MiR-135a overexpression promoted viability, migration, and invasion, but inhibited apoptosis of NCI-H1650 and NCI-H1975 cells. 31 Our subsequent cell biology experiments supported our results that the overexpression of mir-135a-5p could inhibit the invasion of adenocarcinoma cells, and the overexpression of mir-542-3p could promote the proliferation of adenocarcinoma cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study also reported that miR-135a inhibited the migration and invasion of gastric cancer cells by targeting JAK2 [14]. With regards to the role of miR-135a in NSCLC, Zhang et al found that the expression of miR-135a was reduced in the sera of NSCLC patients and was related to poor prognosis [15]. Additionally, it has been reported that the overexpression or restoration of miR-135a represses proliferation and facilitates apoptosis of tumor cells by its target genes c-Myc in renal cell carcinoma [16], JAK2 in lymphoma [17], and ROCK1 in gastric cancer [18].…”
Section: Introductionmentioning
confidence: 99%